Income Inequality and Political Polarization - Waldemar Marz (Center for Economic Studies and ifo Institute (CESifo), 2024)
Value issues such as climate policy, immigration, or identity politics are among the most polarizing policy issues in the U.S. and other high-income countries. That polarization has been rising over the last decades. I investigate a novel channel of income inequality and political campaign contributions on party polarization on the value dimension that is independent of changing voter preferences. In a model of two-dimensional party competition, I show analytically how rising income inequality brings parties' economic policies closer together if campaign contributions are an important factor for electoral success. This lets sensitive voter groups switch their party allegiance and pushes parties to try to distinguish themselves by increasingly focusing on value policy dimension. Income growth, a rising salience of the value issue, and low voter turnout exacerbate this polarization channel. The analysis suggests possible ways forward: 1) a stricter regulation of campaign finances and 2) framing climate primarily as an economic policy issue that puts distributional implications (and remedies) front and center.
Keywords: D63; H23; P16; Q52; Q54; 330; political economy; climate policy; polarization; voting; values